PROBLEMATIKA PENGUJIAN PERATURAN PERUNDANG-UNDANGAN (JUDICIAL REVIEW) PADA MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI - Achmad, Achmad; Mulyanto, Mulyanto (Yustisia, 2013)
ABSTRACTThe aim of this research is to determine the judicial review problems by Supreme Court and Constitutional court. Using empirical and normative approach, data collected by literature studies, interviews, Focus Group Discussion (FGD) and observation. Data were analyzed by using the hermeneutics (interpretation) and deductive method.This research reveals that the legal framework of judicial review by Supreme Court and Constitutional Court are the Article 24 A paragraph (1) and Article 24 paragraph C (1) Indonesia basic law 1945. Constitutional court follow up the legal framework by issued PMK No. 06/PMK/2005 on guidelines of the judicial review procedure, while supreme court follow up the legal framework by issued supreme court regulation No 1/2011 There are two problems on judicial review by supreme court and constitutional coourt. First, conceptually, the implementation of judicial review by supreme court and constitutional court will make hard the control of norms herarchy in the manner of constitution enforcement. Second, operationally, the implementation of a judicial review by Supreme Court and the constitutional Court will create a conflict between state body due to the disparities on the verdict and regulation interpre- tation they have dealt with.Keywords: Judicial Review, Supreme Court, Constitutional courtABSTRAKPenelitian ini bertujuan mengetahui problematika pengujian peraturan perundang-undangan oleh Mahkamah Agung dan Mahkamah Konstitusi. Penelitian ini menggunakan pendekatan normatif sekaligus empiris. Pengumpulan data melalui Studi kepustakaan, Wawancara, Focus Group Discussion (FGD) dan Observasi. Data dianalisis dengan menggunakan metode hermeneutik (interpretasi) di samping deduktif. Hasil penelitian menunjukkan Pengaturan judicial review oleh Mahkamah Agung dan Mahkamah Konstitusi diatur dalam ketentuan Pasal 24 A ayat (1) dan Pasal 24 C ayat (1) UUD NRI 1945. Pelaksanaannya oleh MK ditindak lanjuti melalui PMK No 06/PMK/2005 tentang Pedoman Beracara dalam Perkara Pengujian Undang-Undang sedangkan oleh MA ditindaklanjuti melalui Peraturan Mahkamah Agung No. 1 Tahun 2011. Problematika judicial review melalui Mahkamah Agung dan Mahkamah Konstitusi, Pertama, secara konseptual pelaksanaan pengujian peraturan perundang-undangan ditangan MA dan MK akan menyulitkan integrasi pengawalan hirarki norma mulai dari perda sampai UUD dalam rangka penegakkan konstitusi. Kedua, secara operasional pelaksanaan judicial review antara MA dan MK akan menimbulkan konflik antar lembaga diakibatkan dari perbedaan putusan atau penafsiran peraturan perundang-undangan yang ditangani.Kata kunci: Pengujian peraturan perundangan, Mhkamah Agung, Mahkamah Konstitusi